Molecular Mechanisms of SERT in Platelets: Regulation of Plasma Serotonin Levels - Mercado, Charles P. (American Society for Pharmacology and Experimental Therapeutics, 2010)
The serotonin transporter (SERT) on platelets is a primary mechanism for serotonin (5HT) uptake from the blood plasma. Alteration in plasma 5HT level is associated with a number of cardiovascular diseases and disorders. Therefore, the regulation of the transporter’s activity represents a key mechanism to stabilize the concentration of plasma 5HT. There is a biphasic relationship between plasma 5HT elevation, loss of surface SERT, and depletion of platelet 5HT. Specifically, in platelets, plasma membrane SERT levels and platelet 5HT uptake initially rise as plasma 5HT levels are increased but then fall below normal as the plasma 5HT level continues to rise. Therefore, we propose that elevated plasma 5HT limits its own uptake in platelets by down-regulating SERT as well as modifying the characteristics of SERT partners in the membrane trafficking pathway. This review will summarize current findings regarding the biochemical mechanisms by which elevated 5HT downregulates the expression of SERT on the platelet membrane. Intriguing aspects of this regulation include the intracellular interplay of SERT with the small G protein Rab4 and the concerted 5HT-mediated phosphorylation of vimentin.